Leasing Church Property Owned by a Religious Institute: Canons 1297; 1277; and 638 - Golden, Paul L. (CLSA advisory opinions, 2001-2005, 2001)
We are an international religious institute of pontifical right. Our province has an opportunity to lease an old college building and some grounds to the state university system. We would like to sell the property, but the state law prohibits the local university from purchasing the property. The property is valued at 1.5 million dollars. We have no foreseeable use for this building. The university is willing to lease the property for fifty years. Along with a modest fee, the university will completely renovate the building and pay for all ordinary maintenance for the duration of the lease. Our constitutions and statutes are silent on the issue of leasing. What permissions are needed to validly and licitly make this transaction? Do we follow the rules about alienation?